Pertanggungjawaban Pidana Terhadap Direktur Perseroan Terbatas Atas Tindak Pidana Penggelapan Pajak Studi Putusan Jambi Nomor 155/PID.SUS/2022/PN JMB - Refalia, Salsa; Sepriani, Sarnida; Rasji, Rasji (Jurnal Ilmiah Wahana Pendidikan, 2024)
In this writing, we critically examine the juridical basis of criminal liability for the Director of PT. Jambi Tulo Pratama regarding his tax evasion. Where by deliberately using a tax invoice. So, from this there is a violation of a tax obligation carried out by the taxpayer (Article 38 of the KUP Law). In the crime of embezzlement there are objective elements and subjective elements. And also the concepts of 3 (three) types of concepts in criminal liability, namely, Criminal Without Fault, Strict Liability (strict liability or absolute responsibility) and Vicarious Liability (vicarious liability). The judge's consideration is also important in a case or problem. The judge's consideration is an important stage in the criminal justice process where the judge examines the facts revealed during the trial. These considerations play an important role in determining whether the defendant is guilty or not and in determining the appropriate punishment. The judge's considerations will be included in a decision, where a good decision will fulfill the 3 aspects in a balanced manner.